Amos Decker : Redemption - Book 5 - Baldacci, David (New York : Grand Central Publishing, 2020)
"Decker is visiting his hometown of Burlington, Ohio, when hes approached by a man named Meryl Hawkins. Hawkins is a convicted murderer. In fact, hes the very first killer Decker ever put behind bars. But hes innocent, he claims. Now suffering from terminal cancer, its his dying wish that Decker clear his name. Its unthinkable. The case was open and shut, with rock solid forensic evidence. But when Hawkins turns up dead with a bullet in his head, even Decker begins to have doubts. Is it possible that he really did get it wrong, all those years ago? Deckers determined to uncover the truth, no matter the personal cost. But solving a case this cold may be impossible, especially when it becomes clear that someone doesnt want the old case reopened. Someone who is willing to kill to keep the truth buried, and hide a decades-old secret that may have devastating repercussions ..."--from Amazon.com.
Keywords: Decker, Amos -- (Fictitious character) -- Fiction; Murder -- Investigation; Fiction; Judicial error -- Fiction; Cold cases (Criminal investigation) -- Fiction; Memory disorders -- Fiction; Ohio -- Fiction; Detective and mystery fiction; Thrillers (Fiction)